2020
DOI: 10.1038/s41598-020-78217-1
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative profile, losses and chemical composition of silage soybean genotypes amended with sugarcane levels

Abstract: The experiment aimed to evaluate the fermentative and nutritional profile of the silage of four soybean plant genotypes (BRS 333 RR, Pampeanas: C50, C60, and C70) ensiled with levels of sugarcane (0, 25, 50, 75, and 100%). The experiments were conducted in a completely randomized design, in factorial scheme 4 × 5 (four soybean genotypes and five levels of sugarcane inclusion) with four replicates. Silages with 100% soybean plant presented the highest levels of butyric acid (P < 0.001) and ammoniacal nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Such results are considered desirable because they are below 10% [ 15 ], which indicates no excessive breakdown of proteins to ammonia, characterizing proper silage fermentation. According to Zanine et al [ 16 ], NH 3 -N below 10% is acceptable as it does not cause intoxication and it improves the voluntary intake of silage by animals.…”
Section: Discussionmentioning
confidence: 99%
“…Such results are considered desirable because they are below 10% [ 15 ], which indicates no excessive breakdown of proteins to ammonia, characterizing proper silage fermentation. According to Zanine et al [ 16 ], NH 3 -N below 10% is acceptable as it does not cause intoxication and it improves the voluntary intake of silage by animals.…”
Section: Discussionmentioning
confidence: 99%
“…Kung Jr. et al (2003) reported the use of urea as an additive cause which increased in the silage pH, resulting in the inhibition of unwanted microorganisms. Zanine et al, (2020) stated that the release of ammonia, due to the use of urea, reduces the growth of yeasts and molds, and consequently, reduces DM losses.…”
Section: Dry Matter Loss and Recoverymentioning
confidence: 99%
“…N 2 O and NH 3 -N produced through protein decomposition by microorganisms affect the nutritional value of the feed. The decomposition of carbohydrates and proteins can lead to feed losses of up to 10% ( 13 ). In addition, during CH 4 generation, the complex OM is first decomposed into monosaccharides, amino acids, fatty acids, etc., through the hydrolysis-acidification stage.…”
Section: Introductionmentioning
confidence: 99%